Factors influencing the success of cross-border projects in Africa: a case study of ten projects. (24th September 2021) - Moodley, Rajeshree; Steyn, Herman; Bond-Barnard, Taryn Jane
Africa's economic growth depends on direct foreign investment, primarily through global projects. However, literature on success factors for global/cross-border projects in Africa is non-existent. This paper reports on a study of ten projects, with a combined value of US680 million, executed by a South African company in six other African countries. Best practices and success factors for cross-border projects were investigated, using a modified nominal group technique, a Delphi survey and thematic analysis. The top five success factors identified for African cross-border projects are: 1) front-end loading (FEL); 2) top management support; 3) planning, execution and control (including risk management); 4) leadership and establishing trust; 5) stakeholder satisfaction. A model of the success factors and best practices framework for African cross-border projects is proposed. The paper contributes to the development of project execution strategies to improve African cross-border project performance.